Biological control and plant growth promotion properties of Streptomyces albidoflavus St-220 isolated from Salvia miltiorrhiza rhizosphere - Du, Yongxi; Wang, Tielin; Jiang, Jingyi; Wang, Yiheng; Lv, Chaogeng; Sun, Kai; Sun, Jiahui; Yan, Binbin; Kang, Chuanzhi; Guo, Lanping; Huang, Luqi (Frontiers in Plant Science, 2022)
Root rot disease caused by Fusarium oxysporum is a devastating disease of Salvia. miltiorrhiza, and dramatically affected the production and quality of Sa. miltiorrhiza. Besides the agricultural and chemical control, biocontrol agents can be utilized as an additional solution. In the present study, an actinomycete that highly inhibited F.oxysporum was isolated from rhizosphere soil and identified as based on morphological and molecular characteristics. Greenhouse assay proved that the strain had significant biological control effect against Sa. miltiorrhiza root rot disease and growth-promoting properties on Sa. miltiorrhiza seedlings. To elucidate the biocontrol and plant growth-promoting properties of St-220, we employed an analysis combining genome mining and metabolites detection. Our analyses based on genome sequence and bioassays revealed that the inhibitory activity of St-220 against F. oxysporum was associated with the production of enzymes targeting fungal cell wall and metabolites with antifungal activities. Strain St-220 possesses phosphate solubilization activity, nitrogen fixation activity, siderophore and indole-3-acetic acid production activity in vitro, which may promote the growth of Sa. miltiorrhiza seedlings. These results suggest that St. albidoflavus St-220 is a promising biocontrol agent and also a biofertilizer that could be used in the production of Sa. miltiorrhiza.